Super-earth of 8 M[earth] in a 2.2-day orbit around the K5V star K2-216 - Persson, Carina M.; Heeren, Paul (Arxiv, 2018)
The KESPRINT consortium identified K2-216 as a planetary candidate host star in the K2 space mission Campaign 8 field with a transiting super-Earth. The planet has recently been validated as well. Our aim was to confirm the detection and derive the main physical characteristics of K2-216b, including the mass. We performed a series of follow-up observations: high resolution imaging with the FastCam camera at the TCS, the Infrared Camera and Spectrograph at Subaru, and high resolution spectroscopy with HARPS (ESO, La Silla), HARPS-N (TNG), and FIES (NOT). The stellar spectra were analyzed with the SpecMatch-Emp and SME codes to derive the stellar fundamental properties. We analyzed the K2 light curve with the Pyaneti software. The radial-velocity measurements were modelled with both a Gaussian process (GP) regression and the floating chunk offset (FCO) technique to simultaneously model the planetary signal and correlated noise associated with stellar activity. Imaging confirms that K2-216 is a single star. Our analysis discloses that the star is a moderately active K5V star of mass 0.70+/-0.03 Msun and radius 0.72+/-0.03 Rsun. Planet b is found to have a radius of 1.75+0.17-0.10 Rearth and a 2.17-day orbit in agreement with previous results. We find consistent results for the planet mass from both models: 7.4+/-2.2 Mearth from the GP regression, and 8.0+/-1.6 Mearth from the FCO technique, which implies that this planet is a super-Earth. The planet parameters put planet b in the middle of, or just below, the gap of the radius distribution of small planets. The density is consistent with a rocky composition of primarily iron and magnesium silicate. In agreement with theoretical predictions, we find that the planet is a remnant core, stripped of its atmosphere, and is one of the largest planets found that has lost its atmosphere.
Im Text ergibt sich "Mearth" aus M und dem Erdsymbol 🜨 (Radkreuzzeichen)
Gesehen am 07.08.2020